O processo de desidentidade na categoria bancária: um estudo sobre o nexo causal do desgaste mental - Vieira, Tatiana Varela (2013)
This research was supported by Socio-historical Psychology and aimed to: identify the causal link between the mental strain of the bank worker and labor relations; understand the existing relations between the moment of bank merger and the increase of workers who develop mental disorders and investigate the mental illness and the bank worker health care. From the Sociohistorical perspective, we consider the individual and the society, the subjectivity and the objectivity integrated and constituents of a whole, in constant dialectical and transformative relationship. Given this, we decided to develop a qualitative analysis using the Analysis Centers (Aguiar and Ozella, 2006) as a methodological option, to have the opportunity to examine the human and social phenomena in its dynamic process. The subjects of this study were bank employees who became ill and underwent merger process in the institutions where they worked. These subjects were invited to participate in the study at sites previously chosen, and secured ethical procedures, we conducted semi-structured interviews that were recorded. After the interviews were transcribed, grouped into pre-indicators and core indicators, which were analyzed according to the theoretical basis. Some categories were fundamental to the development of the research: subjectivity, work and identity. Because through them we can understand the individual inserted in its totality, belonging to a social environment and representative of his own characteristics, but changeable. The term "Subjective Dimension of Reality", coined by Furtado (2002), "Identity and Metamorphosis", studied by Ciampa (2005) and "Mental Strain" conceptualized by Seligmann-Silva (2011) are the basis for understanding the research. The workers who were interviewed present processes of de-identification caused by mental, physical and subjective strain. Through the research, we identified that there is a causal link between the working conditions lived by them and the mental strain occurred